2010
DOI: 10.3389/fnagi.2010.00009
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic hypothesis of aging-related cognitive dysfunction

Abstract: This brief review will focus on a new hypothesis for the role of epigenetic mechanisms in aging-related disruptions of synaptic plasticity and memory. Epigenetics refers to a set of potentially self-perpetuating, covalent modifications of DNA and post-translational modifications of nuclear proteins that produce lasting alterations in chromatin structure. These mechanisms, in turn, result in alterations in specific patterns of gene expression. Aging-related memory decline is manifest prominently in declarative/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 146 publications
(224 reference statements)
2
91
1
3
Order By: Relevance
“…This sparse code may be due to particular features of DG neurons such as the high levels of depolarization before action potential threshold is reached (Barnes and McNaughton, 1980), a different transcriptional repression profile (Penner et al, 2010), and perhaps the number of spikes elicited to a given behavior (Leutgeb et al, 2007). This sparse code theoretically allows the DG to store a large amount of nonoverlapping information, but the code in the DG tends to use the same neurons for several different representations .…”
Section: Discussionmentioning
confidence: 99%
“…This sparse code may be due to particular features of DG neurons such as the high levels of depolarization before action potential threshold is reached (Barnes and McNaughton, 1980), a different transcriptional repression profile (Penner et al, 2010), and perhaps the number of spikes elicited to a given behavior (Leutgeb et al, 2007). This sparse code theoretically allows the DG to store a large amount of nonoverlapping information, but the code in the DG tends to use the same neurons for several different representations .…”
Section: Discussionmentioning
confidence: 99%
“…The aged brain differs drastically from its adult counterpart in terms of gene expression programs (204), which are thought to contribute to age-associated memory impairments (269). Recently, two studies have shown that age-related epigenetic differences might account for cognitive decline during aging.…”
Section: The Aging Brainmentioning
confidence: 99%
“…For example, Rubenstein-Taybi syndrome, a disorder characterized by numerous physical defects and behavioral deficits, is caused by mutations in the gene for CBP (Petrij et al, 1995). Moreover, the results discussed above indicate that HDAC inhibitors enhance memory formation and could therefore potentially form the basis of pharmacotherapies for disorders of learning and memory, including age-associated cognitive decline and Alzheimer's disease (Abel and Zukin, 2008;Chuang et al, 2009;Penner et al, 2010a). Although this latter possibility is only beginning to be explored in human patients, the validity of this idea has already been confirmed in animal models.…”
Section: Histone Acetylationmentioning
confidence: 99%